144 Equity and Inclusive Excellence Programs in Medical Institutions in the United States: A cross-sectional survey - Oyku Celik; Sergio M Navarro; Sergio Navarro (Journal of Clinical and Translational Science)
Objectives/Goals: Equity and inclusivity initiatives among medical schools and residency training programs may promote the benefits of demographic and experiential experiences among trainees at multiple training levels. The purpose of this study was to evaluate recent trends in available offerings at medical institutions in the United States. Methods/Study Population: A systematic search of each medical institution’s public domain was conducted to methodically collect and analyze programs at the pre-undergraduate medical education (pre-UME), UME, graduate medical education (GME), and post-GME training levels in the United States. A supplemental search was conducted for any associated efforts at the pre-UME, UME, GME, and post-GME training levels. Categorization of offerings specific to underserved and gender-specific populations was conducted, in addition to national organization partnerships. Changes to institutional offerings were also evaluated. Results/Anticipated Results: The survey identified 82 offerings at the pre-UME, 56 offerings at the UME, 40 offerings at the GME, and 17 offerings at the post-GME level across 155 medical institutions evaluated in the USA. Sixty-five offerings focused on underserved populations and 73 for gender-related populations, with 12 national association partnership programs identified. Recent changes, including reorganization and closure, were noted in 6% of the medical institutions evaluated. Discussion/Significance of Impact: Equity and inclusivity programs remain prevalent at the undergraduate medical education levels, focusing on underserved and gender-related populations. Regional variability and increasing tapering at post-graduate medical education levels show the need for adaptation for effective integration in medical education.